Daniel Assoumou Mba leaves the CTA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
After 12 years as Director of CTA Daniel Assoumou Mba has now completed his assignment. From the outset he has led his institute with discretion and courtesy. During these years the tasks, personnel and budget of the Centre have expanded to create...